TUAN GURU DALAM PUSARAN KONTESTASI POLITIK DI LOMBOK TENGAH (STUDI MOTIF DAN AKSI POLITIK) - Amrillah, Muhammad (Universitas Islam Negeri Mataram, 2021)
Tuan guru's character in the Lombok Community encourages Tuan Guru to be involved in practical politics so that it has an impact on da'wah activities. This study uses a descriptive qualitative approach, data collected by the method of observation, documentation and interviews. This study resulted in a fact that the involvement of the guru - Tuan Guru in Praya Subdistrict, Central Lombok in politics was motivated by their capacity and role in society, but then the role shifted towards